A Vision of the Chilean Spanish from the Historical of Sociolinguistics (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
In this paper, a general global vision of theoretical, methodological and practical aspects of Latin American Spanish historical research field, and Chilean Spanish, in particular, is given. The scope of the first approaches is oriented to the definition of a frame within which the dialect in question is linguistically situated. Then, some relevant elements of the historical research are discussed: sociolinguistic factors such as regional origin, social class and economical class of the documents’ authors; textual and pragmatic considerations, such as text structure and style, moreover, sampling corpus criteria. Finally, as an epilog of the discussion, some diachronic elements of the Chilean Spanish analyzed are taken into account, essentially, in scribes’ documents of the colonial periods.